STROBILUS EXTRACTIVES OF THUJA ORIENTALIS AS NOVEL ANTIBACTERIAL AGENT AGAINST SOME PATHOGENIC BACTERIA - DEVALEENA MUKHERJEE,; ANUSHREE SINGHA RAY,; KUNTAL BHATTACHARYA,; GOUTAM CHANDRA, (International Journal of Pharma and Bio Sciences, 2016)
Thuja orientalis is a well known red cedar commonly used as an externally applied tincture or ointment for the treatment of ringworm, warts and thrush. Antibacterial potentiality of the crude extract and different solvent extracts of the strobilus of Thuja orientalis was evaluated on microbial strains like gram negative Pseudomonas fluorescens, Pseudomonas putida and gram positive Bacillus mycoides, Bacillus licheniformis using agar well diffusion method during the present study. Chloroform: methanol (1:1 v/v) extracts showed the best result against the test bacteria. M.I.C. values of the aforesaid extract were found to be 0.36 mg/ml and 0.96 mg/ml against Pseudomonas fluorescens and Pseudomonas putida respectively while 1.09 mg/ml and 1.12 mg/ml for Bacillus mycoides and Bacillus licheniformis respectively. The chloroform: methanol (1:1 v/v) extract of strobilus of Thuja orientalis may act as a novel source to obtain an effective antibacterial agent.